Local Energy Transition and Technical Knowledge in the Southern Cone: A Sociological Approach [Conhecirnento Técnico E Transição Energética No Cone Sul: Uma Abordagern Sociológica] [Conocirniento Técnico y Transición Energética en el Cono Sur: Un Enfoque Sociológico] - Parker-Gumucio, C (Universidad de los Andes, Bogota Colombia, 2020)
Social research on the transition to renewable energies has focused on understanding public policies and social movements. Energy knowledge plays an important practical, normative, and social role that influences actors’ approaches to this transition, which has been scarcely studied at local or community levels, let alone in the Global South. A comparative methodology is used to study cases of communes in Argentina and Chile. The results are presented using a variety of data sources to explore the frameworks of the energy matrix and energy projects, revealing the role of technical knowledge in building local agency. This article presents a theoretical discussion and conclusions that include proposals for the future development of a more local, inclusive, committed and deliberative transition process, based on local technical expertise in renewable energies. © 2020, Universidad de los Andes, Bogota Colombia. All rights reserved.